2015
DOI: 10.1007/s13277-015-3512-1
|View full text |Cite
|
Sign up to set email alerts
|

Strong expression of paired-like homeodomain transcription factor 1 (PITX1) is associated with a favorable outcome in human osteosarcoma

Abstract: Paired-like homeodomain transcription factor 1 (PITX1) has been implicated as a tumor suppressor in various cancers. However, the biological and clinical significance of PITX1 in osteosarcoma has not been fully elucidated. Here, we studied the expression and clinical significance of PITX1 in 6 normal lower limb bone tissue specimens and 35 osteosarcoma tissue samples by immunohistochemistry. PITX1 was expressed in all normal tissues (6/6, 100 %) and in 85.7 % (30/35) of tumor tissues (P > 0.05). In addition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…PITX1 function is critical for TPC proliferation and survival, while its decline enables squamous differentiation. Increased PITX1 expression has also been observed in KRAS mutant colorectal cancers (Watanabe et al, 2011) and acute lymphoblastic leukemia (Nagel et al, 2011), while its increased expression correlates with good prognosis in melanoma (Osaki et al, 2013), osteosarcoma (Kong et al, 2015), prostate, lung, liver, and gastric cancers (Calvisi et al, 2011;Chen et al, 2007), indicative of context-dependent functions. Indeed, we found PITX1 cooperates with SOX2 and TRP63 to govern an SCC-specific transcriptional network.…”
Section: Discussionmentioning
confidence: 99%
“…PITX1 function is critical for TPC proliferation and survival, while its decline enables squamous differentiation. Increased PITX1 expression has also been observed in KRAS mutant colorectal cancers (Watanabe et al, 2011) and acute lymphoblastic leukemia (Nagel et al, 2011), while its increased expression correlates with good prognosis in melanoma (Osaki et al, 2013), osteosarcoma (Kong et al, 2015), prostate, lung, liver, and gastric cancers (Calvisi et al, 2011;Chen et al, 2007), indicative of context-dependent functions. Indeed, we found PITX1 cooperates with SOX2 and TRP63 to govern an SCC-specific transcriptional network.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a decreased PITX1 expression has been revealed in bronchial (17,18), hepatic (19), colorectal (20), pancreatic (21), prostatic (22) and gastric malignancies (15,16). It has also been demonstrated that the level of PITX1 is correlated with patient survival; patients with higher PITX1 levels exhibit a longer median overall survival in human osteosarcoma (24). The reduced expression of PITX1 is also independently correlated with shorter patient survival and may serve as a prognostic marker in colorectal carcinoma (32).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have also indicated that PITX1 expression is downregulated in certain types of malignant cancer, including oral squamous cell carcinoma (13), esophageal (14), gastric (15,16), lung (17), breast (18), hepatic (19), colorectal (20), pancreatic (21) and prostatic cancer (22), as well as malignant melanoma (16,23). The strong expression of PITX1 is associated with a favorable outcome in human osteosarcoma (24). PITX1 expression also serves as a novel biomarker for the prediction of patient prognosis in oral epithelial dysplasia (25) and may be a predictive biomarker of human head and neck squamous cell carcinoma chemosensitivity (26).…”
Section: Introductionmentioning
confidence: 99%
“…PITX2 is involved in specifying pulmonary venous myocardial sleeves, suppression of a default left-atrial sinus node, and conditional knockout of the Pitx2c transcript has been linked to increased AF susceptibility in mice. 4244 Activation of PITX1 was suggested to be associated with tumor suppression in various cancers, 45, 46 but the function of PITX1 in cardiac function has not been well-understood. The second novel locus is at 53kb upstream of RASSF8, encoding a candidate tumor suppressor protein, RASSF8 , 47 but the association of RASSF8 and cardiac physiology remains unclear.…”
Section: Discussionmentioning
confidence: 99%